Genome-Wide Characterization and Analysis of the bHLH Transcription Factor Family in Suaeda aralocaspica, an Annual Halophyte With Single-Cell C4 Anatomy - Wei, Xiaowei; Cao, Jing; Lan, Haiyan (Frontiers in Genetics, 2022)
Basic helix-loop-helix (bHLH) transcription factors play important roles in plant growth, development, metabolism, hormone signaling pathways, and responses to abiotic stresses. However, comprehensive genomic and functional analyses of bHLH genes have not yet been reported in desert euhalophytes. Suaeda aralocaspica, an annual C4 halophyte without Kranz anatomy, presents high photosynthetic efficiency in harsh natural habitats and is an ideal plant for identifying transcription factors involved in stress resistance. In this study, 83 bHLH genes were identified in S. aralocaspica and categorized into 21 subfamilies based on conserved motifs, gene structures, and phylogenetic analysis. Functional annotation enrichment revealed that the majority of SabHLHs were enriched in GO terms and KEGG pathways involved in the response to stress conditions, as transcription factors. A number of cis-acting elements related to plant hormones and stress responses were also predicted in the promoter regions of SabHLHs, which were confirmed by expression analysis under various abiotic stress conditions (NaCl, mannitol, low temperature, ABA, GA3, MeJA, and SA); most were involved in tolerance to drought and salinity. SabHLH169(076) proteins localized in the nucleus had transcriptional activity, which gene expression could also be affected by different light qualities. This study is the first comprehensive analysis of the bHLH gene family in S. aralocaspica. These data will facilitate further characterization of their molecular functions in the adaptation of desert plants to abiotic stress.